Multi‐analytical approach for the study of Neolithic pottery from the Great Dolmen of Zambujeiro (Evora, Portugal)– a preliminary study - Manhita, Ana (2014)
The chemical and mineralogical composition of the Zambujeiro Dolmen ceramics was analysed using stereomicroscopy (SM), X‐ray diffraction (XRD), in‐situ X‐ray fluorescence spectroscopy (XRF) and scanning electron microscopy with X‐Ray energy dispersive spectroscopy detection (SEM‐EDS). Analyses have shown that quartz is the most abundant mineral in the ceramics, with feldspars, especially alkali feldspars (Na, K), being also present in the majority of the samples. Titanium‐iron oxide minerals, like ilmenite, were also detected in some samples. The nature of the clay minerals varies among the samples, but it was possible to identify illite/smectite which can help approximate the firing temperature of the ceramics. Overall, the ceramics’ composition is consistent with the geology of the area, confirming the local provenance of the materials used for its production. Analysis of the organic content was done using gas chromatography coupled with mass spectrometry (GC‐MS). The ceramic's organic content is likely from vegetable origin, which can be inferred from the presence of a high content of unsaturated fatty acids, various steroids of vegetable origin (campesterol, stigmasterol and beta‐sitosterol), absence of cholesterol (steroid of animal origin) and a ratio of fatty acids C16:C18 > 1. Biomarkers for the presence of resins from the genus Pinus, the diterpenoid derivatives such as dihydroabietic and isopimaric acids, were identified in some samples. The reason for the use of resinous materials can be attributed to their sealing or gluing properties, but they could also bring a characteristic flavour to the materials stored in the ceramic vessels.